2004
DOI: 10.1097/00001813-200411000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré syndrome in a patient with metastatic colon cancer receiving oxaliplatin-based chemotherapy

Abstract: We report Guillain-Barre syndrome (GBS), developed in a patient with metastatic colon cancer, receiving oxaliplatin-based chemotherapy. The 53-year-old patient was treated with first-line chemotherapy consisting of oxaliplatin 45 mg/m2, 5-fluorouracil 450 mg/m2 and folinic acid 200 mg/m2, all given on the same day in a weekly schedule. After 13 weeks of treatment and a cumulative oxaliplatin dose of 585 mg/m2, the patient developed unsteadiness of gait, dysphagia, and weakness of both the upper and lower limbs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 12 publications
0
24
1
2
Order By: Relevance
“…Therefore, when motor and autonomic symptoms are predominant and/or there is an absence of sensory involvement, an alternative diagnosis should be considered. As an example, platinum‐based compounds have been rarely associated with acute inflammatory demyelinating polyradiculoneuritis in patients with solid tumor, which appears to respond well to standard immunotherapy. Additionally, it is important to be aware that treatment with more than one neurotoxic agent may increase the likelihood of peripheral neuropathy, which may be associated with involvement of the autonomic system (especially parasympathetic heart innervation) …”
Section: Clinical Aspects Of Pipnmentioning
confidence: 99%
“…Therefore, when motor and autonomic symptoms are predominant and/or there is an absence of sensory involvement, an alternative diagnosis should be considered. As an example, platinum‐based compounds have been rarely associated with acute inflammatory demyelinating polyradiculoneuritis in patients with solid tumor, which appears to respond well to standard immunotherapy. Additionally, it is important to be aware that treatment with more than one neurotoxic agent may increase the likelihood of peripheral neuropathy, which may be associated with involvement of the autonomic system (especially parasympathetic heart innervation) …”
Section: Clinical Aspects Of Pipnmentioning
confidence: 99%
“…All platinum compounds typically produce 'coasting' where neuropathy progresses for weeks to several months after drug treatment ends, and our findings may be correlatedwiththisphenomenon.However,sincethemotor symptomssharesimilaritieswiththoseobservedintheacute neurotoxicity of oxaliplatin, it could also be speculated that animmuno-mediatedNa + channeldysfunctionplaysarolein thepathogenesisofdelayedneuropathy.Notably,allpatients developedacutesymptomsofcoldhypersensitivity,and2pa-tients muscle discomfort. In agreement with this hypothesis, Christodoulou et al [13] reported the occurrence of Guillan-Barrèsyndromeinapatientwithmetastaticcoloncancer receivingoxaliplatin-basedchemotherapy.Theauthorsargue that elevation of pro-inflammatory cytokines such as tumor necrosisfactor-alphaandinterleukin-6,inducedbyoxaliplatin mayrepresenttherelevantcausallinkinvolvedinthecascade ofeventswhichhaveledtotheimmune-mediateddemyelinationinthispatient.Interestingly,Noronhaetal. [14]recently reported the case of a woman with metastatic carcinoma of theileocecalregion,whoreceivedFOLFOXand,afterpartial remission with minimal side-effects, developed a mild selflimitedepisodeofimmune-mediatedhemolyticanemia.Our preliminary observations indicate that delayed sensorimotor polyneuropathy is a complication which must be considered forpatientsreceivingadjuvantoxaliplatin-containingchemotherapy.…”
Section: Discussionmentioning
confidence: 59%
“…[16,17] Okzaliplatin, vinkristin, L-asparginaz, daunorubisin gibi bazı kemoterapi ajanları GBS gelişimi ile ilişkili bulunmuştur. [8][9][10] Tümör hücrelerinden eksprese edilen onko-nöral antijenlerin, anti-onko-nöral veya anti-myelin antikorları uyararak nöron hasarını başlattığı düşünül-mektedir. Ayrıca platin bazlı kemoterapinin TNFalfa ve IL-6 gibi sitokinleri artırdığı ve nöronlarda enflamatuvar hasarı tetiklediği de gösterilmiştir.…”
Section: Discussionunclassified
“…[6] Literatürde, kanserle ve antikanser tedaviyle iliş-kili GBS olguları bildirilmiştir. [7][8][9][10] Burada kanser ve febril nötropeni ile ilişkili olabilecek nadir bir durum olan GBS deneyimimizi sunmak istedik.…”
unclassified